If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9x+8x+5=-6x-9+4
We move all terms to the left:
-9x+8x+5-(-6x-9+4)=0
We add all the numbers together, and all the variables
-9x+8x-(-6x-5)+5=0
We add all the numbers together, and all the variables
-1x-(-6x-5)+5=0
We get rid of parentheses
-1x+6x+5+5=0
We add all the numbers together, and all the variables
5x+10=0
We move all terms containing x to the left, all other terms to the right
5x=-10
x=-10/5
x=-2
| 4K-8=k+19 | | -6+3p=p+10 | | 11-7x=-5+4(2x+4) | | p/2=5p-27 | | -16y=-384 | | -2t-4+10t=3+9t | | -2x-97-6x=31 | | 1+3b=15+b | | x=0.375 | | 8n+6(1+6n)=226 | | 2-2n=-4n | | 10y+3-2=70-3y | | 4x-6x=x+4 | | 10(4+3x)=-80 | | n/9=6n-159 | | -10-9j=-7j | | -6-2k+7k=-3k+2k | | 2-8b=-5b-10 | | 4(2+8x)=34+6x | | -3x+8-2x=10-4x | | 36.36=7g+3.74 | | -5b+2b=-6 | | 71=5v+11 | | 36.36=7g.3.74 | | -5(x-5)+4+4=35 | | 13x+9=6x+2 | | 13(4y+8)=5(91+5y) | | 5r=+45 | | 10x^2-20x+30=0 | | -12=4(3x-6) | | -15-4x=6x-3 | | 15=20x-65 |